Nasal high‐frequency oscillatory ventilation and CO2 removal: A randomized controlled crossover trial. Issue 9 (12th July 2018) - Bottino, Roberto; Pontiggia, Federica; Ricci, Cinzia; Gambacorta, Alessandro; Paladini, Angela; Chijenas, Vladimiras; Liubsys, Arunas; Navikiene, Jurate; Pliauckiene, Ausrine; Mercadante, Domenica; Colnaghi, Mariarosa; Tana, Milena; et al.
Abstract: Objective: To compare short‐term application of nasal high‐frequency oscillatory ventilation (nHFOV) with nasal continuous positive airway pressure (nCPAP). Working Hypothesis: nHFOV improves CO2 removal with respect to nCPAP in preterm infants needing noninvasive respiratory support and persistent oxygen supply after the first 72 h of life. Study Design: Multicenter non‐blinded prospective randomized crossover study. Patient Selection: Thirty premature infants from eight tertiary neonatal intensive care units, of mean ± SD 26.4 ± 1.8 weeks of gestational age and 921 ± 177 g of birth weight. Methodology: Infants were randomly allocated in a 1:1 ratio to receive a starting treatment mode of either nCPAP or nHFOV delivered by the ventilator CNO (Medin, Germany), using short binasal prongs of appropriate size. A crossover design with four 1‐h treatment periods was used, such that each infant received both treatments twice. The primary outcome was the mean transcutaneous partial pressure of CO2 (TcCO2 ) value during the 2‐h cumulative period of nHFOV compared with the 2‐h cumulative period of nCPAP. Results: Significantly lower TcCO2 values were observed during nHFOV compared with nCPAP: 47.5 ± 7.6 versus 49.9 ± 7.2 mmHg, respectively, P = 0.0007. A different TcCO2 behavior was found according to the random sequence: in patients starting on nCPAP, TcCO2 significantly decreased from 50.0 ± 8.0 to 46.6 ± 7.5 mmHg during nHFOV ( P = 0.001). In patients starting on nHFOV, TcCO2 slightly increased from 48.5 ± 7.8 to 49.9 ± 6.7 mmHg during nCPAP ( P = 0.13). Conclusions: nHFOV delivered through nasal prongs is more effective than nCPAP in improving the elimination of CO2 .